2019
DOI: 10.1186/s13046-019-1347-0
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of YBX1 with G3BP1 promotes renal cell carcinoma cell metastasis via YBX1/G3BP1-SPP1- NF-κB signaling axis

Abstract: Background Renal cell carcinoma (RCC) is a deadly urological tumor that remains largely incurable. Our limited understanding of key molecular mechanisms underlying RCC invasion and metastasis has hampered efforts to identify molecular drivers with therapeutic potential. With evidence from our previous study revealing that nuclear overexpression of YBX1 is associated with RCC T stage and metastasis, we investigated the effects of YBX1 in RCC migration, invasion, and adhesion, and then characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 53 publications
2
50
0
Order By: Relevance
“…Moreover, in other cancer types, patients with mutations of YB-1 and ABCB-1 genes have decreased overall survival time. Recently, a study established the importance of YB-1 in mccRCC cell migration and adhesion by activation of nuclear factor kappa B (NF-κB) signalling pathway [39]. Therefore, it is a logical extension to investigate the association of YB-1/ ABCB-1 and sunitinib-resistance development in mccRCC tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in other cancer types, patients with mutations of YB-1 and ABCB-1 genes have decreased overall survival time. Recently, a study established the importance of YB-1 in mccRCC cell migration and adhesion by activation of nuclear factor kappa B (NF-κB) signalling pathway [39]. Therefore, it is a logical extension to investigate the association of YB-1/ ABCB-1 and sunitinib-resistance development in mccRCC tumors.…”
Section: Discussionmentioning
confidence: 99%
“…For some mRNAs, such as that of G3BP1, the data on YB-1 involvement in translational control are contradictive. Some researchers report that YB-1 enhances G3BP1 mRNA translation through binding to the 5 UTR [125,126], while others deny such regulation [127,128]. The difference in conclusions can be explained by the presence or absence of regulatory RBPs whose binding and activity are modulated by YB-1.…”
Section: Yb Proteins In Translation Stimulationmentioning
confidence: 99%
“…The results indicated that the NF-κB signaling pathway, which was demonstrated to be dysregulated and functional in the ROS-related chemotherapeutic resistance of ccRCC cells [24,25], might intervene in the regulation of G6PD expression. To verify this hypothesis, the protein expression pattern of several important functional factors of NF-κB pathway, including p105, p50, p65, pIκBα (S32+S36), and IκBα, which have been proved to participate in signaling transduction and closely link to ccRCC tumorigenesis [24,25,28,41], was examined in NAC-or H 2 O 2treated ACHN, 786-O and Caki-1 cells. The results from Western blot showed that the levels of pIκBα, the most abundant inhibitory molecule of NF-κB [41], were reduced by ROS depletion, but there were increased following ROS accumulation in all these three cells.…”
Section: Ros Positively Regulated G6pd and Nf-κb Signaling Pathway Inmentioning
confidence: 99%